Pengaruh Kompetensi dan Loyalitas Terhadap Kinerja Karyawan PT Pegadaian CP Ponorogo Yang Dimediasi Oleh Kemampuan Kerja - Ade Syahrizal; Agatha Tyagitha; Istini Istini; Ahmad Shofi Muzadi; Chamariyah Chamariyah (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
Ade Syahrizal, 2024. The Influence of Competence and Loyalty on the Empolyee Performance of PT Pegadaian CP Ponorogo Mediated by Work Ability. Wijaya Putra University Postgraduate Program Surabaya. This type of research is explanatory research, the approach used is a quantitative approach, the research sample is 46 people. The analysis tool uses Smart PLS (Partial Least Square). Research objectives: 1) To determine and analyze the influence of competence on the employee performance of PT Pegadaian CP Ponorogo. 2) To determine and analyze the influence of competence on the work ability of the PT Pegadaian CP Ponorogo. 3) To determine and analyze the influence of loyalty on the employee performance of PT Pegadaian CP Ponorogo. 4) To determine and analyze the indirect influence of loyalty on the work ability of PT Pegadaian CP Ponorogo. 5) To determine and analyze the indirect influence of work ability on the employee performance of PT Pegadaian CP Ponorogo. 6) To determine and analyze the indirect influence of competence on the employee performance of PT Pegadaian CP Ponorogo which is mediated by work ability. 7) To determine and analyze the indirect influence of loyalty on the employee performance of PT Pegadaian CP Ponorogo. The research results show that: 1) Competence has a positive and significant effect on employee performance as evidenced by the original sample value of 0.369 and p-values ​​of 0.000. 2) Competence has a significant positive effect on work ability as proven by the original sample value of 0.373 and p-values ​​of 0.002. 3) Loyalty has a positive and significant effect on employee performance as evidenced by the original sample value of 0.492 and p-values ​​of 0.000. 4) Loyalty has a significant positive effect on work ability as proven by the original sample value of 0.378 and p-values ​​of 0.000. 5) Work ability has a significant positive effect on employee performance as evidenced by the original sample value of 0.378 and p-values ​​of 0.000. 6) Competence has a positive and significant effect on employee performance which is mediated by work ability as evidenced by the original sample value of 0.141 and p-values ​​of 0.013. 7) Loyalty has a positive and significant effect on employee performance which is mediated by work ability as evidenced by the original sample value of 0.186 and p-values ​​of 0.001.